Influence of landscape structures on river water quality at multiple spatial scales: A case study of the Yuan river watershed, China - Qiyu Xu (Elsevier, 2021)
Significant attention has recently been given towards understanding the hydrological effects of landscape structures. However, few studies have quantified the relationships between landscape structures and river water quality at different spatial scales. Here, we evaluated the influence of landscape structures, including structural composition and spatial configuration, on river water quality at scales ranging from riparian zones to entire regions. Water quality parameters (pH, Cl−, SO42−, DO, NO3−−N, NH4+−N, TP, and heavy metals) were determined from 38 sample sites in August 2018 during the wet season and January 2019 during the dry season. Landscape structures explained more of the water quality variation (ranging from 7% to 36%) in the near-distance buffer zones (100, 300, and 500 m), but slightly less (ranging from 2% to 27%) in the long-distance buffer zones (1000 m and entire regions). Landscape structures had the greatest impact on water quality at the 300-m buffer zone, and of all explanatory variables of landscape, joint effects between landscape composition and landscape configuration accounted for more than half of the variation in water quality. Moreover, different regional division methods considerably impacted the measured correlation between landscape structures and water quality. Compared with zonal division, a larger basin area division of sub-basin enhanced the correlation and associated significance between landscape composition and water quality. Concomitantly, the input of exogenous pollutants weakened the influence of mean dendritic stream length on the relationships between landscape structures and water quality. Overall, this study provides new insights into the relationships between landscape structures and river water quality. In future studies, selecting an appropriate regional division method is critical for revealing the effects of landscape structures on water quality. Furthermore, strengthening land-use management in the buffer zones near river banks is critical for protecting river water quality.